"دور الإدارة الإلكترونية في تحقيق النجاح الاستراتيجي - دراسة ميدانية في مؤسسة اتصالات الجزائر بالوادي " - فتيحة, خلاوي; محمد الناصر, زبيدي; منير, احميد (جامعة الوادي - University of Eloued, 2023)
"هدفت هذه الدراسة إلى التعرف على دور الإدارة الإلكترونية في تحقيق النجاح الاستراتيجي دراسة حالة مؤسسة اتصالات الجزائر بالوادي، ولتحقيق أغراض هذه الدراسة تم استخدام المنهج الوصفي التحليلي وتمثلت متغيرات الدراسة في الإدارة الإلكترونية، النجاح الاستراتيجي. ولتحقيق أهداف البحث تم الاعتماد على استمارة استبيان المكونة من جزئين خصص الأول للبيانات الشخصية للمبحوثين، أما الثاني تم تقسيمه إلى محورين حيث تضمن المحور الأول متغير الإدارة الإلكترونية موزع على أربع أبعاد (المقومات الإدارية، المقومات التقنية، المقومات البشرية، وأخيرا المقومات المالية) وكل بعد مكون من أربعة عبارات، كما تضمن المحور الثاني متغير النجاح الاستراتيجي الذي يضمن أربعة أبعاد (الاستمرارية، التكيف، النمو، والتعلم) وكل بعد يحتوي على أربعة عبارات. وتم توزيع (72) استمارة استبيان على العاملين في مؤسسة اتصالات الجزائر فرع الوادي بجميع فروعها وتم استرجاع الاستمارات الصالحة للتحليل (65) أي بنسبة (90.28%) وتم اعتماد على البرنامج الإحصائي للعلوم الإنسانية (SPSS)‏ للحصول على النسب والتكرارات والأوساط الحسابية وكذلك الارتباط والتأثير بين متغيرات البحث. ومن أهم النتائج التي توصلت إليها الدراسة الحالية وجود علاقة ارتباط موجبة بين الإدارة الإلكترونية والنجاح الاستراتيجي، كما تبين أن هناك اثر للإدارة الإلكترونية في تحقيق النجاح الاستراتيجي. وأوصت الدراسة إلى اقتناع والتزام متخذي القرار(الإدارة العليا) بتطبيق الإدارة الإلكترونية والتجنيد الجيد لأفراد ذوى العلاقة وتخصيص الموارد اللازمة للقيام بعملية تطبيق الإدارة الإلكترونية، نظرا لأهميتها في تحقيق النجاح الاستراتيجي. ""The aim of this study was to identify the role of electronic management in achieving strategic success. The case study of the Algerian telecommunications institution in the valley was conducted, and to achieve the purposes of this study, the descriptive analytical approach was used and the study variables were represented in electronic management, strategic success. To achieve the research objectives, a two-part questionnaire form was used, the first was devoted to the personal data of the researchers, the second was divided into two axes, where the first axis included the electronic management variable distributed over four dimensions (administrative, technical, human, and finally financial components) and each dimension consisted of four phrases, and the second axis included the strategic success variable, which guarantees four dimensions (continuity, adaptation, growth, and learning) and each dimension contains four phrases. (72) Questionnaire forms were distributed to the employees of Algeria Telecom El-Oued branch in all its branches, and the forms valid for analysis were retrieved (65), that is, by (90.28%), and the statistical program for the humanities (SPSS) was adopted to obtain the ratios, repetitions, computational circles, as well as the correlation and influence between the research variables. One of the most important findings of the current study is that there is a positive correlation between electronic management and strategic success, and it was also found that there is an impact of electronic management in achieving strategic success. The study recommended the conviction and commitment of decision-makers (senior management) to the application of electronic management and the good recruitment of related personnel and the allocation of resources necessary to carry out the process of applying electronic management, given its importance in achieving strategic success."
Keywords: إدارة الإلكترونية، نجاح استراتيجي، اتصالات الجزائر، SPSS; Electronic management, strategic success, Algeria Telecom, SPSS.